Phoebe's baby bombshell - Harroway, J. C. (Harlequin medical, 2023)
After one hot night...she has shocking news! Independent neonatal surgeon Phoebe always plays it safe. Until she meets fellow surgeon Zach at a conference. Never has her desire for anyone made her so breathless--or reckless! Believing she won't see the sexy bachelor again, Phoebe dives headfirst into a wild night. But two months later, she has two problems: Zach's back in her world and she's expecting his baby!